Analysing food-derived interactions between tourists and sika deer (Cervus nippon) at Miyajima Island in Hiroshima, Japan: implications for the physical health of deer in an anthropogenic environment. Issue 1 (2nd January 2018) - Usui, Rie; Funck, Carolin
ABSTRACT: Sika deer ( Cervus nippon ) on Miyajima Island in Hiroshima, Japan, are accustomed to a human environment and close tourist-deer interactions occur. In 2008, city officials banned deer feeding in response to an increasing number of human-deer conflicts. Nevertheless, this regulation remains ineffective. In this study, food-derived interactions between tourists and deer were analyzed, and a faecal analysis was conducted to examine the effects of potentially beneficial bacteria on the digestive system of deer. Over 64 hours of observation, a total of 397 tourist-deer interactions were recorded. Most interactions involved tourists' food purchases from street stalls (49.6%). The initiator of each interaction was recorded for 267 events (67.3%), and it was found that deer initiated nearly twice as many interactions as tourists (tourists: 93 events; deer: 174 events). However, feeding occurred in only 11.5% of deer-initiated interactions, while feeding occurred in 50.5% of tourist-initiated interactions. The analysis of gastrointestinal bacterial community compositions showed that deer in the tourism district possessed a lower portion of the order Lactobacellales than deer in the non-tourism district. This was presumably due to different food sources, indicating that the human-influenced environment, of which feeding is one element, could affect the physical health of the deer.